2017
DOI: 10.5194/se-8-499-2017
|View full text |Cite
|
Sign up to set email alerts
|

Soil Atterberg limits of different weathering profiles of the collapsing gullies in the hilly granitic region of southern China

Abstract: Abstract. Collapsing gullies are one of the most serious soil erosion problems in the tropical and subtropical areas of southern China. However, few studies have been performed on the relationship of soil Atterberg limits with soil profiles of the collapsing gullies. Soil Atterberg limits, which include plastic limit and liquid limit, have been proposed as indicators for soil vulnerability to degradation. Here, the soil Atterberg limits within different weathering profiles and their relationships with soil phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 58 publications
(53 reference statements)
1
33
2
Order By: Relevance
“…Positive correlation between PL and PI agrees with Larney et al (1988) and Tsegaye et al (2017). However, our results of negative correlations between CEC and ALs, CEC and PI are in contrast with positive correlation between soil ALs and CEC reported by Deng et al (2017). Soil resistivity exhibits strong positive correlations with OM (1.000**), soil resistivity and shear strength (1.000**), and positive correlation at 5% level exists between soil resistivity and CBR (0.634*).…”
Section: Results Of Statistical Analysescontrasting
confidence: 99%
See 1 more Smart Citation
“…Positive correlation between PL and PI agrees with Larney et al (1988) and Tsegaye et al (2017). However, our results of negative correlations between CEC and ALs, CEC and PI are in contrast with positive correlation between soil ALs and CEC reported by Deng et al (2017). Soil resistivity exhibits strong positive correlations with OM (1.000**), soil resistivity and shear strength (1.000**), and positive correlation at 5% level exists between soil resistivity and CBR (0.634*).…”
Section: Results Of Statistical Analysescontrasting
confidence: 99%
“…Negative correlation between % sand and MC is in line with similar results by Senjobi and Ogunkunle (2011) and Olorunfemi et al (2016). The strong negative correlation between % sand and ALs agrees with similar results by Deng et al (2017) and Igwe et al (2013), while correlation between % sand and PI (− 1.000**) is in line with similar result by Roy and Bhalla (2017) who reported that increase in sand content results in decreased PI.…”
Section: Results Of Statistical Analysessupporting
confidence: 90%
“…Considering the results as indicated by black dots in Figure 3, the LL and I P in particular increased with increasing pH from 2.0 to 6.0 and then decreased as pH increased further to 10.0 in Figure 3. As LL, PL, and I P depend primarily on soil texture, which is related to the particle-size distribution [7,28], the changes in LL, PL, and I P with pH resulted from changes in soil particle size. As shown in Figure 4, the proportion of soil particles with sizes less than 0.01 mm decreased as pH decreased from 6.0 to 2.0.…”
Section: Effects Of Ph On the Physical Characteristics Of Simulated Smentioning
confidence: 99%
“…This issue has been frequently reported in Southeast Asian countries with tropical climates [3][4][5], where squalls with high rain intensity are a major contributor to the erosion caused by water [6]. The physical characteristics of soils such as attraction force among soil particles, Atterberg limits, which include the liquid limit (LL) and plastic limit (PL) and indicate the soil's vulnerability to degradation, and soil particle size also contribute to the erosion [7,8]. For example, low-LL soils easily transform into viscous liquids with increasing water content and are easily transported by rainwater, making them susceptible to soil water erosion.…”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of the high-steep slope of a collapsing wall and the mechanism of collapsing erosion, the engineering characteristics and preferential flows have also been investigated for the profile of the collapsing wall. Some researchers analyzed the spatial variations of shear strength and hydraulic properties in collapsing gullies and evaluated their effects on the collapsing erosion mechanism [14,[18][19][20]. Additionally, researchers have also investigated the variations of chemical composition and physical properties with soil depth in the collapsing gullies and found that the contents of gravel and sand increase while the amount of sesquioxides decreases with an increase of soil depth [21,22].…”
Section: Introductionmentioning
confidence: 99%